Surveiller, faire croire et punir: The Body of Evidence in Luis Rafael Sánchez’s La pasión según Antígona Pérez - Bettaglio, Marina (Latin American Theatre Review, 2012)
A Foucauldian reading of Luis Rafael Sánchez’s play La pasión según AntígonaPérez reveals the importance of the body as a site of punishment as well as of propagandisticstrategies in the manipulation of public opinion in the imaginary state of Molina. Surveillanceand punishment, alluded to in my title, are thus aided by a complex media apparatus intent onmaking people believe—“faire croire”—in the official story fabricated by the dictator, CreónMolina, in this Puerto Rican version of the Sophoclean drama. In this context, Antigone’s burialof two combatants killed in a rebellious act acquires a profoundly political and subversivemeaning. Her defiant act deprives the penal system of its signifier by removing a crucial partof the tyrant’s repressive strategy.